Trends in angiotensin receptor/neprilysin inhibitor (ARNI) prescribing across multi-Centre, multi-ethnic heart failure population - C Chelfi Zhi, Fei Chua; B. K., Chung; Hwei Sung, Ling; K. C., Cheah; S. L., Kwa; J., Namasoo; C. H., ChaI; P. W., Ting; M. J., Khaw; J. K.W., Wong; A.Z. Y., Koh; W. K., Ho; et al. (European Society of Cardiology, 2025)
Background: Angiotensin receptor-neprilysin inhibitors (ARNIs) are recommended in clinical guidelines for the management of heart failure with reduced ejection fraction (HFrEF) due to their proven benefits in reducing mortality and hospitalization rates. However, real-world data on the use, and dosing of ARNI therapy remain limited especially in middle income country. Objectives:We aim to study the prescribing patterns of ARNI among HFrEF patients in heart failure (HF) clinic. Methods: This is a retrospective cohort study encompassing HF clinic patients followed up in 10 hospitals from 1st January 2021 to 30th June 2023. Results: Overall, the cohort of 416 patients consisted of 78.1% men with a mean age of 55.6 (13.5) years. Majority of the population was local indigenous population (46.1%), followed by Malay (29.5%) and Chinese (23.8%). The most prevalent comorbidity was hypertension (64.7%), followed by dyslipidemia (52.9%), ischemic heart disease (44.2%) and diabetes mellitus (38.8%). At baseline, 71.2% of patients were on renin-angiotensin-aldosterone system (RAAS) blockers. Following their first clinic visit, RAAS blocker prescriptions increased to 82.9%, reaching 88.5% at three months and 88.9% at sixmonths. At the time of recruitment to the HF clinic, 16.9% of patients were already receiving ARNI therapy. This rate increased to 27.5% by their first clinic visit, 35.1% at three months, and 38% at six months. At baseline, only 43.1% of patients were receiving 50% or more of the recommended ARNI dosage. After the first clinic visit and subsequent optimization at three and six months, this proportion increased to 57.9%, 67.1%, and 72.8%, respectively. Conclusions: ARNI prescription as initiation is low but the dosage and use of ARNI has risen over time. This study reflects the gap in treatment patterns between clinical trials and real-world practice.